2022
DOI: 10.3389/fpsyg.2022.756343
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Managers’ and HR-Officers’ Experiences and Perceptions of Participating in Alcohol Prevention Skills Training: A Qualitative Study

Abstract: ObjectiveThe objective of this study was to explore Swedish managers’ and HR-officers’ experiences and perceptions of skills training including a development and implementation of an alcohol policy.MethodsSemi-structured interviews were conducted with Swedish managers (n = 44) and HR-officers (n = 9) from nine different organizations whom had received skills training and an organizational policy implementation. The interviews were analyzed using thematic analyses.ResultsIn total, nine themes were identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The lack of significant findings in one of the outcome evaluations suggests that implementing APMaT’s intervention components may have been challenging. Nevertheless, the qualitative study focusing on managers’ experiences as a part of KAPRI indicated a positive recollection of the skills development training among managers, whereas any policy alterations seemed to have gone unnoticed by the participants (Martinez et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of significant findings in one of the outcome evaluations suggests that implementing APMaT’s intervention components may have been challenging. Nevertheless, the qualitative study focusing on managers’ experiences as a part of KAPRI indicated a positive recollection of the skills development training among managers, whereas any policy alterations seemed to have gone unnoticed by the participants (Martinez et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…APMaT was effective in increasing managers’ inclination to intervene through increased confidence to initiate a dialogue (Elling et al , in press), but not in reducing employees’ hazardous alcohol use (Elling et al , unpublished data). Moreover, qualitative interviews aimed at exploring managers’ experiences and perceptions regarding APMaT suggested that implementing the organisational alcohol policy, specifically concerning policy dissemination among managers, appeared challenging (Martinez et al , 2022). Understanding the factors that constitute an obstacle of successful prevention programmes (Thørrisen et al , 2019a) is warranted.…”
Section: Introductionmentioning
confidence: 99%